ABDURRAUF SINGKEL’S INSAN KAMIL CONCEPT TO ANSWER THE PROBLEM OF SEXUAL CONSENT, CHILDFREE, NATURE AND NURTURE IN URBAN SOCIETY - Ihsan, Nur Hadi; Sa'ari, Che Zarrina Binti; Sansayto, Tistigar; Indallah, Sayyid Muhammad (AKADEMIKA: Jurnal Pemikiran Islam, 2024)
This article aims to analyze Abdurrauf Singkel's concept of Insan Kamil to address the problems of sexual consent, childfree, and nature and nurture which frequently arise in urban society. These issues are a common phenomenon in contemporary urban society due to their materialistic lifestyle and the pursuit of worldly goals by denying their true nature (fitrah). Sufism's concept of "Insan Kamil" depicts the ideal human being from every perspective—that is, the ideal human being as he is by nature. This concept of the perfect human will serve as an antidote to the three problems above, each of which is a deviation from the essence of human nature. This paper is a qualitative library research that analyzes data using an analytical descriptive method. This study concludes that, first and foremost all of these issues stem from the same root cause which is a denial of human nature. As a concept of the perfect human, Insan Kamil is a manifestation of achieving the pinnacle of humanity based on true human nature. Insan Kamil is also a condition of servitude to the highest degree or ihsan. Therefore, this concept is relevant to overcoming the root problems of sexual consent, childfree, and nature and nurture which stem from the denial of one's nature. By becoming Insan Kamil, someone can place himself according to his nature in the right and proper place.